22 Retrospective Regional Audit of In-Patient Assessment of Left Ventricular Systolic Function and Guideline-Recommended Prescription of Eplerenone following St-elevation Myocardial Infarction. (6th June 2015) - Jackson, Alice M; Mailey, Jonathan; Rocchiccioli, J Paul; Campbell, Ross T; Sonecki, Piotr
Abstract : Introduction: The Eplerenone Post-Acute Myocardial Infarction Heart Failure Efficacy and Survival Study (EPHESUS) trial demonstrated that eplerenone reduces all-cause mortality and death or hospitalisation for cardiovascular events in patients with symptomatic left ventricular (LV) systolic dysfunction (ejection fraction ≤40%) or diabetes following ST-elevation myocardial infarction (STEMI). Current national and international guidelines recommend initiation of eplerenone in this patient group. We conducted a retrospective audit of assessment of LV systolic function and subsequent prescribing of eplerenone in eligible patients presenting with acute STEMI over a 4-month period. Aims and objectives: Establish what proportion of patients presenting with STEMI had in-patient assessment of LV systolic function Identify whether LV systolic function assessment was performed qualitatively or quantitatively Determine what proportion of eligible patients were prescribed eplerenone on hospital discharge Methods: Patients from NHS Greater Glasgow and Clyde (GG&C) who underwent primary percutaneous coronary intervention (PPCI) for STEMI were retrospectively (01/08/13–30/11/13) identified using the coronary intervention patient-database at the West of Scotland Regional Heart and Lung Centre (Golden Jubilee National Hospital). Data were collected using electronic patient records and national radiology archive. Qualitative assessment was defined as a subjective description of LV systolic function (normal, mild, moderate or severe impairment). Quantitative assessment was defined as a documented ejection fraction (EF). Patients were considered eligible for eplerenone if they had a qualitative assessment of LV systolic function documented as moderately or severely impaired, or EF ≤ 40% on quantitative assessment, and symptomatic LV systolic dysfunction or diabetes. Results: 172 patients were identified. 90% of the total population had in-patient assessment of LV systolic function (Table 1 ). All of these patients had qualitative assessment (Table 1 ). LV systolic function was quantitatively assessed in 27% (10% modified Simpson's Biplane method, 11% estimated EF, 5% unspecified) (Table 1 ). 8% of patients were considered eligible for eplerenone (Table 2 ). Of those eligible, eplerenone was appropriately prescribed on discharge in 21% (Table 2 ). Conclusions: This audit indicates that national and international guidelines for the assessment and management of LV systolic function post-STEMI are not being adhered to within this region. Identifying those with LV systolic dysfunction post-STEMI is not only of importance for the optimisation of drug therapy, but also for patient selection for implantable defibrillators. The wider implications of LV systolic dysfunction include DVLA-imposed restrictions on driving and critical illness policies. Potential barriers to compliance with guidelines include time-constraints, training and shorter inpatient stay since the adoption of PPCI. These factors may explain the low prescribing rate of eplerenone in eligible patients.